PROFESSIONAL COMMITMENT OF SCHOOL TEACHERS: TEACHER EDUCATION - Maheshwar, Amrita (THE PRIMARY TEACHER, 2011)
Professional commitment refers to a mindset reflecting loyalty and willingness to give one’s all to a particular person, principle or plan of action. A teacher’s commitment may be reflected with reference to the following six dimensions of her/his role or obligation– Commitment to learner, Commitment to institution, Commitment to work, Commitment to achieving excellence, Commitment to society and Commitment to human values. This research paper compares the degree of professional commitment of secondary teachers in relation to their sex and the socio economic status. A comparative study of teacher’s professional commitment with its six dimensions may be instructive in understanding the commitment dynamics and achieving the goal of quality education.